Initial vegetative and reproductive development of coffee cultivars in Vale do Ribeira Paulista - Carvalho, Alex Mendonça de; Botelho, Cesar Elias; Ferreira, André Dominghetti; Teramoto, Erico Tadao; Lima, Amador Eduardo; Miyazaki Junior, Felipe Shiniti; Guerreiro Filho, Oliveiro (Semina: Ciências Agrárias, 2022)
This research is related to the performance evaluation of twelve Coffea arabica cultivars in Vale do Ribeira Paulista, in order to generate consistent information for the technical recommendation for cultivation in the region. The experiment was set in February 2018, at the Experimental Campus of the São Paulo State University "Júlio de Mesquita Filho" - UNESP in Registro, SP, Brazil, in a spacing of 3.00x0.60 m, in a randomized block design with three replications. The following parameters were evaluated: stem diameter, number of plagiotropic branches, plant height, number of internodes of plagiotropic branches, length of the first plagiotropic branch, incidence of brown spots and phoma leaf spot, infestation by leaf miner and yield. The results showed a good adaptation of all cultivars to growing conditions in Vale do Ribeira Paulista, with higher and faster vegetative development of large coffee cultivars. The productive potential of cultivars in the first harvest was similar to the performance of the same cultivars in traditional growing regions, with emphasis on 'Arara' and 'Catucaí Amarelo 24/137', with about 55 bags ha-1 of processed coffee. There was no incidence of rust disease in the experimental evaluation period, unlike other biotic agents such as leaf miner, phoma-spot and brown eye spot.